166 Psychological distress and wellbeing in UK olympic and paralympic athletes. (3rd March 2020) - Ranson, Craig; Leyland, Sandra; Board, Lisa; Jaques, Rod; Currie, Alan
Abstract : Background: Despite the known mental health benefits of exercise the prevalence of mental health symptoms and disorders in high performance athletes appears to be slightly higher than in the general population and athletes with disabilities may be especially at risk. However data is scarce and valid comparisons are difficult. Objective: To gauge the prevalence of psychological distress and the level of wellbeing amongst UK Olympic and Paralympic programme athletes. Design: Cross-sectional questionnaire cohort study. Setting: UK Olympic and Paralympic, summer and winter sport athletes. Patients (or Participants): 394 athletes from 29 sports. Interventions (or assessment of risk factors): Between October 2018 and June 2019, participants completed the Kessler Psychological Distress Scale (K10) and the World Health Organisation-Five Well-Being Index (WHO5) questionnaires that indicate levels of psychological distress and subjective wellbeing respectively. Main outcome measurements: Percentage of athletes reporting low, moderate, high and very high psychological distress. Percentage of athletes reporting high and low wellbeing. Results: 24% of athletes reported high or very high psychological distress. More Paralympic that Olympic athletes reported high/very high distress (27% vs 22%). The mean distress score was comparable to age matched population samples. 19% of athletes reported low psychological wellbeing and this was more common in Paralympic athletes than Olympic athletes (23% vs 17%). The mean wellbeing score was comparable to age matched population samples. Conclusions: UK Olympic and Paralympic athletes report psychological distress and wellbeing levels similar to aged matched populations. Paralympic athletes have slightly higher levels of distress and lower wellbeing than Olympic athletes and this may relate to disability specific stressors. Sport programmes should have robust mental health support plans that includes regular athlete screening and commensurate support services with additional specific support for athletes with disabilities.